Proceedings of the Symposium of Aeronautical and Aerospace Processes, Materials and Industrial Applications Presented at the XXV International Materials Research Congress - Cancun 2016 - Zambrano-Robledo, P.; Salinas-Rodriguez, A.; Almeraya Calderon, F.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents selected contributions to the Symposium of Aeronautical and Aerospace Processes, Materials and Industrial Applications of the XXV International Materials Research Congress (IMRC). Each chapter addresses scientific principles behind processing and production of materials for aerospace/aeronautical applications. The chapter deals with microstructural characterization including composites materials and metals.  The second chapter deals with corrosion in aerospace components is a large and expensive problema for aerospace industry. Finally, the last chapter covers modeling and simulation of different processes to evaluate and optimize the forming process. This book is meant to be useful to academics and professionals.
Part 1: Microstructure and characterization -- chapter 1. Microstructural characterization of inconel 718 for future ultrasonic fatigue testing -- chapter 2. Geometry tool influence on the microstructure of mmc al-sic friction stir welds -- chapter 3. Study of decomposition of martensite in fv535 steel -- chapter 4. On the effect of hysteresis in shock isolators for aeronautical applications -- part 2: corrosion in aerospace materials -- chapter 5: effects of heat treatments in corrosion behaviour of hvof sprayed ni-based alloy coatings -- chapter 6. Electrochemical study of 17-4 and 17-7 ph stainless steels used in the aeronautical industry -- chapter 7. Corrosion behavior of a austempered ductil iron used in the aeronautical industry, evaluated on acid solutions -- chapter 8. . Design of wind tunnel for testing stress corrosion cracking -- chapter 9. Citric acid passivation of 15-5ph and 17-4ph stainless steel used in the aeronautical industry -- part 3: Numerical modelling -- chapter 10. Grain size effect during hot ring rolling process using nickel base superalloy -- chapter11. Finite element modelling of friction stir spotwelding (fssw) of ti-6al-4v -- chapter 12. Parametric effects in hybrid lap joints of composite materials use in aircraft structures.
Keywords: Materials -- Analysis; Materials; Surfaces (Physics).; Aerospace engineering; Astronautics; Characterization and Analytical Technique; Materials Engineering; Surface and Interface and Thin Film; Aerospace Technology and Astronautics